2005
DOI: 10.1501/dishek_0000000038
|View full text |Cite
|
Sign up to set email alerts
|

Di̇şheki̇mleri̇ Ve Di̇şheki̇mli̇ği̇ Öğrenci̇leri̇ni̇n Di̇ji̇tal Radyografi̇ Hakkindaki̇ Bi̇lgi̇, Tutum Ve Davranişlarinin Değerlendi̇ri̇lmesi̇

Abstract: The aim of this study was to evaluate the knowledge, attitudes and beliefs of dental students,general dental practitioners and academicians about intraoral digital radiography.For this purpose a questionnaire was administered to dental students, general dental practitioners and academicians investigating their understanding of the principles of digital radiography, their decision criteria to its use, and on the suitability of the topic in the undergradute dental curriculum. Demographic, clinical and electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…0.05). Also, Wenzel et al 18 and Sogur et al 24 found that gender and age were not significant determining factors when using digital radiography.…”
Section: Discussionmentioning
confidence: 98%
“…0.05). Also, Wenzel et al 18 and Sogur et al 24 found that gender and age were not significant determining factors when using digital radiography.…”
Section: Discussionmentioning
confidence: 98%
“…1 Hekimlerin görüntüleme teknikleri konusundaki tercihleri incelendiğinde, dijital sistemler hakkında yeterli bilgiye sahip olmayan hekimlerin konvansiyonel teknikleri kullandıkları görülmektedir. 11 Tüm yeni teknolojilere geçiĢte olduğu gibi konvansiyonel radyografiden FP sistemlerine geçiĢte farklılık ve sorunların ortaya çıkması kaçınılmazdır. Önemli olan bu sorunları ve nedenlerini saptayarak sistemin kullanıĢlı bir hale getirilmesidir.…”
unclassified